The Oxford handbook of participation in organizations (New York, 2010)
"Employee participation encompasses the range of mechanisms used to involve the workforce in decisions at all levels of the organization - whether direct or indirect - conducted with employees or through their representatives. In its various guises, the topic of employee participation has been a recurring theme in industrial relations and human resource management. One of the problems in trying to develop any analysis of participation is that there is potentially limited overlap between these different disciplinary traditions, and scholars from diverse traditions may know relatively little of the research that has been done elsewhere. Accordingly in this book, a number of the more significant disciplinary areas are analysed in greater depth in order to ensure that readers gain a better appreciation of what participation means from these quite different contextual perspectives.